Analysis and Performance Improvement of a Four-Leg Unsignalized Intersection (Case of study: Duta Berlian Intersection, Dramaga, Bogor) - Fatoni, Ahmad; Sudibyo, Tri; Apriadi; Fauzan, Muhammad (Jurnal Teknik Sipil dan Lingkungan, 2025)
The Duta Berlian intersection near IPB University, Dramaga, Bogor experiences severe traffic congestion due to traffic volumes exceeding its capacity, high roadside friction, and the absence of traffic light. This study aims to evaluate the performance of the existing intersection and assess several improvement scenarios to improve intersection’s capacity and level of service (LOS). Traffic volume surveys were carried out using the Classified Turning Movement Counting (CTMC) method during morning and evening peak hours, followed by analysis of capacity, degree of saturation (DS), delay, and queue probability calculations. The 2023 Indonesian Highway Capacity Manual (PKJI 2023) and Ministry of Transportation Regulation No. 96/2015 were used as the analysis method and LOS classification. The analysis showed that the existing condition has DS of 1.08, average delay of 23.3 sec/PCU, queue probability of 93.23%, and LOS C. Four scenarios were tested: approach widening, conversion to a signalized intersection, application of a four-phase signal with right-turn separation, and addition of a left turn on red (LTOR) lane. The optimal scenario combined a minimum widening of 2 m with a four-phase signal and LTOR, reducing DS to 0.70, delay to 12–15 sec/PCU (LOS B), and potentially decreasing accident rates by 20–50%. In conclusion, conversion to a signalized intersection with geometric redesign and traffic flow management significantly improves intersection performance and is recommended to be equipped with yellow box junctions, markings, and signage as a medium-term solution. For a long-term solution, a grade-separated intersection is recommended.